Storage Study of Dehydrated Cauliflower - Gupta, Manoj Kumar; Seghal, V K (Journal of Agricultural Engineering, 2005)
Cauliflower variety no. 71 was cut into 3x3, 4.5x3 and 5x2.5 cm sizes and dehydrated in a mechanical dryer at three different air velocities (40, 50 and 60 m/min )and drying air temperature of 55, 60 and 65degree C.Dehydrtad samples were stored at room temperature for four months and analyzed for vitamin C, rehydration ratio, browning and overall acceptability . At the end of storage period vitamin C losses were 60.27, 56.12, and 61.59 for the cauliflower samples dehydrated at 55, 60 and 65degree C, respectively. Rehydration ratio decreased with the advent of storage period where as browning did not change with the storage period. Sensory evaluation indicated the acceptability of the product, dried under all experimental conditions, after four months of storage.